2013
DOI: 10.5812/hepatmon.9248
|View full text |Cite
|
Sign up to set email alerts
|

Non Alcoholic Fatty Liver Disease in Southern Iran: A Population Based Study

Abstract: BackgroundPopulation based studies on prevalence and risk factors of NAFLD in Iranian population are few. The prevalence of NAFLD and non alcoholic steatohepatitis (NASH) in Iranians varies from 2.9% to 7.1% in general population and 55.8% in patients with type 2 diabetes mellitus.ObjectivesTo determine the prevalence and determinants of non alcoholic fatty liver disease (NAFLD) in a sample of adult Iranian general population.Patients and MethodsThis was a cross-sectional study being performed in Shiraz, south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 33 publications
1
49
0
1
Order By: Relevance
“…Similarly, in many studies waist circumference has been shown as another risk factor for NAFLD [26, 27] while in a study done by Ahad Eshraghian et al [30] it has been shown that WHR is a more accurate risk factor for NAFLD in comparison to waist circumference, where it was introduced as a risk factor for making tree in this study.…”
Section: Discussionmentioning
confidence: 55%
“…Similarly, in many studies waist circumference has been shown as another risk factor for NAFLD [26, 27] while in a study done by Ahad Eshraghian et al [30] it has been shown that WHR is a more accurate risk factor for NAFLD in comparison to waist circumference, where it was introduced as a risk factor for making tree in this study.…”
Section: Discussionmentioning
confidence: 55%
“…[2829] Amirkalali et al . reported a high prevalence rate of NAFLD (43.8%) among adults population in the north of Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a population-based study on 819 individuals indicated that FLD was significantly correlated with BMI, serum glucose, and serum triglyceride and had no significant correlation with serum cholesterol. The prevalence rates of high liver enzyme and grade I, II, and III fatty liver in that study were 8.8%, 21.5%, 16.4%, and 5.1%, respectively (27).…”
Section: Discussionmentioning
confidence: 99%